2018
DOI: 10.1101/398560
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CA3 place cells that represent a novel waking experience are preferentially reactivated during sharp wave-ripples in subsequent sleep

Abstract: (which was not peer-reviewed) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…It is assumed that the activity of hippocampal place cells, which fire in specific locations when animals navigate (O'Keefe and Dostrovsky, 1971), provides a cognitive map in which episodic events are embedded (Mizumori, 2006;Smith and Mizumori, 2006). In support of this idea, it has been shown that networks of hippocampal cells active during wake are reactivated during NREM sleep at compressed timescales (Drieu et al, 2018;Hwaun and Colgin, 2019;Lee and Wilson, 2002), which is important for memory formation (de Lavillé on et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It is assumed that the activity of hippocampal place cells, which fire in specific locations when animals navigate (O'Keefe and Dostrovsky, 1971), provides a cognitive map in which episodic events are embedded (Mizumori, 2006;Smith and Mizumori, 2006). In support of this idea, it has been shown that networks of hippocampal cells active during wake are reactivated during NREM sleep at compressed timescales (Drieu et al, 2018;Hwaun and Colgin, 2019;Lee and Wilson, 2002), which is important for memory formation (de Lavillé on et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Using LFPs recorded from CA1 tetrodes with place cells, SWRs were detected when rats were in the rest box. The detection method followed that described in a previous study 52 . In brief, LFPs were first bandpass filtered between 150 and 250 Hz, followed by a Hilbert transform to estimate the instantaneous wave amplitude of the filtered LFPs.…”
Section: Methodsmentioning
confidence: 99%
“…The first empirical evidence for memory reactivations during sleep came from studies that recorded the hippocampus of rodents during spatial exploration of a maze and showed that cells from places that were co-active during exploration had correlated activity patterns during subsequent periods of non-rapid eye movement (NREM) sleep [8] and that the temporal order of the original sequence during wakefulness was partially preserved during sleep (referred to as 'neural replay') [9]. Since then, a growing number of studies corroborated the occurrence of hippocampal memory reactivations in a variety of species, both during sleep (e.g., [10][11][12][13][14][15][16][17]) and quiet rest (e.g., [18]). Memory reactivations have been closely tied to sharp wave-ripple (SWRs) activity arising from the hippocampus [19] but have also been recorded across a wide range of brain regions (e.g., [20,21]).…”
Section: Memory Reactivations: Pioneering Work In Rodentsmentioning
confidence: 97%
“…The reactivation of memories in sleep appears to be a selective process. In rodents, hippocampal memory traces of novel experiences, compared to familiar experiences, are preferentially reactivated during sleep [14,15] and persist longer [6,8,10]. Neural reactivations in rodents are also amplified for experiences associated with an emotional response [64] or a reward [65], potentially due to coupling of reactivations with dopamine reward signals (e.g., [66,67]) or with amygdala activity [64].…”
Section: Selectivitymentioning
confidence: 99%